Functional nanomaterials and devices VII : selected, peer reviewed papers from the 7th International Workshop on Functional Nanomaterials and Devices, April 8-11, 2013, Kyiv, Ukraine - Nazarov, A. N. (Alexei N.); Lysenko, Volodymyr S.; Flandre, Denis (Advanced materials research ;, 2014)
The volume contains some of the most recent knowledge on Functional Nanomaterials and Devices. The papers are grouped into: 1. semiconductor-on-insulator structures, devices and sensors; 2. physics of new functional nanodevices and sensors; 3. diagnostics methods of nanomaterials and devices; 4. functional nanomaterials in medicine. The first part considers transport phenomena in thin silicon layer near back SiO2-Si interface of the SOI structures fabricated with DELICATE technology, mobility increase in high doped nanowire junctionless multigate MOSFETs; photoconductance and LF noises in the.